Toll-like receptor-4 mediates neuronal apoptosis induced by amyloid β-peptide and the membrane lipid peroxidation product 4-hydroxynonenal - Tang, Sung-Chun; Lathia, Justin D.; Selvaraj, Pradeep K.; Jo, Dong-Gyu; Mughal, Mohamed R.; Cheng, Aiwu; Siler, Dominic A.; Markesbery, William R.; Arumugam, Thiruma V.; Mattson, Mark P. (Experimental neurology, 2008)
The innate immune system senses the invasion of pathogenic microorganisms and tissue injury through Toll-like receptors (TLR), a mechanism thought to be limited to immune cells. We recently found that neurons express several TLRs, and that the levels of TLR2 and TLR4 are increased in neurons in response to energy deprivation. Here we report that TLR4 expression increases in neurons when exposed to amyloid β-peptide (Aβ1–42) or the lipid peroxidation product 4-hydroxynonenal (HNE). Neuronal apoptosis triggered by Aβ and HNE was mediated by jun N-terminal kinase (JNK); neurons from TLR4 mutant mice exhibited reduced JNK and caspase-3 activation and were protected against apoptosis induced by Aβ and HNE. Levels of TLR4 were decreased in inferior parietal cortex tissue specimens from end-stage AD patients compared to aged-matched control subjects, possibly as the result of loss of neurons expressing TLR4. Our findings suggest that TLR4 signaling increases the vulnerability of neurons to Aβ and oxidative stress in AD, and identify TLR4 as a potential therapeutic target for AD.